Khidmah Lughawiyah (Pembinaan Bahasa Arab) Dalam Meningkatkan Penguasaan Kosakata Bahasa Arab Di TKA/TPA - Zulfikar Ahmad; Karina Alifiana Karunia (PT FORMOSA CENDEKIA GLOBAL, 2022)
Arabic is a foreign language that has high literary features. The most basic thing to learn in Arabic is vocabulary. In learning vocabulary, educators should teach in accordance with the context so that it is easy to apply both orally and in writing by students. Through Arabic language development activities, it is expected to be able to help students recognize, understand, and memorize Arabic vocabulary. The implementation of the Arabic language development was carried out at the TKA/TPA Dusun Barue, Lamatti Gantarang Village, Central Sinjai District. The results show that Arabic language development packaged with interesting and innovative materials can increase the Arabic vocabulary of the TKA/TPA Dusun Barue students.